Undergraduates’ Level of Acceptance and Utilization of Moodle Platform for Learning During Covid-19 Pandemic - Ebenezer Omolafe Babalola; Funmilayo Lanre Otunla; Eyiyemi Veronica Omolafe (Indonesian Journal of Multidiciplinary Research, 2023)
This study investigated the undergraduates’ level of acceptance and utilization of Moodle platform for learning at the University of Ilorin. This study adopted descriptive research of the survey type. A random sampling technique was used to select two hundred (200) undergraduates who formed the sample size for this study. The data obtained through the questionnaire was subjected to both descriptive and inferential statistics. Frequency counts and means score was used to answer the research questions, ANOVA was used to test hypothesis one while a t-test was used to test hypothesis two. The findings of this study were: the Undergraduates’ level of acceptance of Moodle platform for learning is negative with a grand mean score less than the benchmark [2.18 2.45]; the Undergraduates’ level of utilization of Moodle platform for learning is negative with the grand mean score less than the benchmark [2.32 2.45]; there was a significant difference in the undergraduates’ level of acceptance of Moodle platform for learning based on the area of specialization [p= .000 0.05]; and there was a significant difference between male and female Undergraduates level of utilization of Moodle platform for learning [p= .026 0.05]. The study concluded that Moodle platform with so many existing features and future potential uses is not broadly accepted and utilized in many universities. It is recommended among others that Universities should implement a platform that supports online learning activities so that it makes it easier for lecturers to engage students virtually and delves further into the obstacles faced by students in online learning activities.